Low-energy impact response of composite sandwich panels with thermoplastic honeycomb and reentrant cores. (November 2020) - Özen, İsmail; Çava, Kutay; Gedikli, Hasan; Alver, Ümit; Aslan, Mustafa
Abstract: In the present study, the low-energy impact response of woven carbon fibre reinforced plastic (CFRP) composite sandwich panels with thermoplastic honeycomb and reentrant cores was investigated experimentally and numerically under three different impact energies (20 J, 40 J and 70 J). The Acrylonitrile Butadiene Styrene (ABS) honeycomb and reentrant core structures were manufactured in-plane and out-of-plane oriented via 3D printer, and adhesively bonded with two CFRP face sheets. The results indicate that the in-plane reentrant core based composite sandwich panel exhibits better impact strength and energy dissipation behavior than the in-plane and out-of-plane honeycomb core based composite sandwich panels. Highlights: 3D printer technology provides advantages in production of the sandwich core structures with complex geometry. Composite sandwich panels can be successfully produced by using thermoplastic core structure and CFRP face-sheets. Reentrant cored composite sandwich panels allow the development of impact strength and energy dissipation ability. FEM presents an effective solution in modeling low-energy impact response of the composite sandwich structures.